The significance of growth shells in development of symmetry, transparency, and refraction of the human lens - Greiling, Teri M.; Clark, Judy M.; Clark, John I. (Frontiers in Ophthalmology, 2024)
Human visual function depends on the biological lens, a biconvex optical element formed by coordinated, synchronous generation of growth shells produced from ordered cells at the lens equator, the distal edge of the epithelium. Growth shells are comprised of straight (St) and S-shaped (SSh) lens fibers organized in highly symmetric, sinusoidal pattern which optimizes both the refractile, transparent structure and the unique microcirculation that regulates hydration and nutrition over the lifetime of an individual. The fiber cells are characterized by diversity in composition and age. All fiber cells remain interconnected in their growth shells throughout the life of the adult lens. As an optical element, cellular differentiation is constrained by the physical properties of light and its special development accounts for its characteristic symmetry, gradient of refractive index (GRIN), short range transparent order (SRO), and functional longevity. The complex sinusoidal structure is the basis for the lens microcirculation required for the establishment and maintenance of image formation.